Mineralogy and sediment grain-size distributions as index of the modern sedimentary processes of Sawa Lake, Mothanna Governorate, Southwestern Iraq - Khaleefah, Usama Q.; Hussein, Meelad A.; Chasib, Sajjad K. (Mesopotamian Journal of Marine Sciences, 2019)
Sawa Lake is located in the southwest of Samawa city, it is of geological significance because it lies in the transitional zone between the sedimentary plain and the western plain, which is semi-desert and relies on the ground water as providing sources. It has a special case in sedimentation. The mineralogical composition of the lake sediments is characterized by Gypsum Calcite, Anhydrite, and Hematite, which is in turn builds different forms of sedimentary structures, including the tuberous, concretion, Nodule, and linear forms, as well as the deposition of calcium carbonate at the bottom of the lake in general. The cones were deposited by Chara algae (biological deposition), which collect sand grains from the atmosphere and connect them with calcium carbonate, these structures in the southern part of the lake are close to the sand dunes. The physical deposition in the lake was based mainly on wind and dust storms and the presence of sand dunes in the south and south-west and some areas in the north-west of the lake. The results of the grain size analyses showed the dominance of sand, more than 80%, and the silt does not exceed 20% while the clay is 1%. The north and south east of the lake, which is far from the movement of sand dunes does not exceed 70%, while the silt reaches 30% and the clay is still about 1%. This process detects the effect of sand dunes movement in the area.